2017
DOI: 10.2217/imt-2017-0127
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Calcitriol and Anticancer Immunotherapy: Vitamin D as the Possible Balance Between Inflammation and Autoimmunity in the Immune-Checkpoint Blockade

Abstract: " We are thus inclined to hypothesize a proportionally better prognostic role respectively for normal basal vitamin D levels and for recovering levels after proper repletion in advanced cancer patients, compared with the worse prognosis of vitamin D deficient patients who are unable to raise their levels. Similarly, the possible predictive role of vitamin D status for response to CKI might follow this proportional strength " First draft submitted: 5 September 2017; Accepted for publication: 25 September 2017; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…It has already been reported that VDR signaling is required for T cell activation and NKT cell development, both of which are important immunological factors for antitumor responses [44,45]. More recently, it has also been demonstrated that VD decreases tumor growth and increases tumor infiltrating CD8+ T cells in breast cancer [46].…”
Section: Vitamin D: Between Mtor and The Immune Systemmentioning
confidence: 99%
“…It has already been reported that VDR signaling is required for T cell activation and NKT cell development, both of which are important immunological factors for antitumor responses [44,45]. More recently, it has also been demonstrated that VD decreases tumor growth and increases tumor infiltrating CD8+ T cells in breast cancer [46].…”
Section: Vitamin D: Between Mtor and The Immune Systemmentioning
confidence: 99%
“…Historically, pancreatic ductal adenocarcinomas have not responded well to monotherapy with immune checkpoint inhibitors when tested in clinical trials [75,76] and this is at least in part due to the poor immunogencity and decreased immune cell infiltrates of these tumors [77]. Vitamin D functions not only as a stromal reprogrammer, but it also modulates the immune system and plays a role in T cell activation, which may alter the tumor microenvironment to make checkpoint inhibitors more efficacious [78,79]. Multiple clinical trials (Table 1) are currently exploring the combination of immune checkpoint inhibitors and Vitamin D analogs (with and without other chemotherapeutics) for the treatment of pancreatic cancer.…”
Section: Checkpoint Inhibition Oncolytic Immunotherapy and Pancrmentioning
confidence: 99%
“…Patients participating in BGB-A317-208 were treated with tislelizumab, a humanized immunoglobulin G4 (IgG)variant monoclonal antibody affecting the immune checkpoint-inhibitory receptor known as programmed cell death protein-1 (PD-1) [15,16]. The BGB-A317-208 context of use was distinct from the published QLQ-HCC18 validation population, with the former consisting of previously treated, unresectable HCC patients.…”
Section: Introductionmentioning
confidence: 99%